Synthesis and properties of 0.8PZT-0.10PZN-0.10PNN ceramics - Nabunmee S. (2014)
The 0.8PZT-0.10PZN-0.10PNN powders were synthesized via a columbite method. Pure perovskite phase was obtained at the calcinations temperature ≥ 900°C. Ceramics with the same composition were fabricated at various sintering temperatures. The densest ceramic with pure phase perovskite was obtained at the sintering temperature of 1250°C for 4 h. The ceramics showed two phase transition at ∼265°C and ∼291°C which correspond to orthorhombic to tetragonal and tetragonal to cubic phase transition, respectively. The obtained ceramics also showed a very high dielectric constant >40000. The ferroelectric properties were investigated and discussed. Copyright © Taylor & Francis Group, LLC.